Arthroscopic Repair of an Isolated Posterior Cruciate Ligament Avulsion - Avinesh Agarwalla, M.D.; Andrew D. Posner, M.D.; Orr Limpisvasti, M.D. (Arthroscopy Techniques)
Posterior cruciate ligament (PCL) injuries are uncommon, with isolated PCL injuries being even more rare. Low-grade injuries are typically managed conservatively. In cases of multiligamentous knee injuries, high-level athletes, or continued instability following nonoperative management, surgical intervention typically comprises PCL reconstruction. Primary repair of isolated injuries has benefits of ligament preservation, early mobilization, and quicker return to activities. The authors describe a technique for knotless arthroscopic primary PCL repair.